Reconnaissance for Radioactive Deposits in the Buckland-Kiwalik District, Candle Quadrangle, Seward Peninsula, Alaska - West, Walter S.; Matzko, John J. (Geological Survey (U.S.), 1952)
A report regarding a reconnaissance done in order to locate radioactive deposits in the Buckland-Kiwalik district, in the Candle Quadrangle in the Seward Peninsula, Alaska.